Conjunctival pyogenic granuloma during pregnancy - Şekkeli,Mehmet Zahid (2021)
ABSTRACT Pyogenic granuloma is a common benign, vascular lesion of the skin and mucosa. Our case was a 34-year-old woman at 28 weeks of gestation. She presented with a complaint of a growing and occasionally bleeding mass on the left lower eyelid conjunctiva for approximately 3 months. On examination, a red, pedunculated fragile lesion on the medial lower eyelid conjunctiva was observed. Ophthalmologic examination revealed that visual acuity was 20/20 in both eyes. Anterior and posterior segment examination was normal bilaterally. The lesion was excised completely under local anesthesia and sent for pathological examination. Histopathological examination revealed multiple vascular structures with small-diameters in the fibrous stroma. Vessels showed strong CD31 expression in immunohistochemical staining. Kaposi sarcoma was excluded due to negative HHV-8 staining. These findings were diagnostic of pyogenic granuloma. The frequency of pyogenic granuloma increases during pregnancy and surgical excision is important in diagnosis and treatment of these patients. This is the first reported case of conjunctival pyogenic granuloma during pregnancy.